2019
DOI: 10.1002/chem.201903935
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐C−C/C−N‐Coupled Light‐Emitting Aliphatic Terpolymers: N−H‐Functionalized Fluorophore Monomers and High‐Performance Applications

Abstract: To circumvent costly fluorescent labeling, five nonconventional, multifunctional, intrinsically fluorescent aliphatic terpolymers (1–5) have been synthesized by C−C/C−N‐coupled, solution polymerization of two non‐emissive monomers with protrusions of fluorophore monomers generated in situ. These scalable terpolymers were suitable for sensing and high‐performance exclusion of CuII, logic function, and bioimaging. The structures of the terpolymers, in situ attachment of fluorescent monomers, aggregation‐induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 84 publications
0
25
0
Order By: Relevance
“…[ 22 ] Indeed, a monomer bearing tertiary amide side chain should endow more rigidity and fluorescence of polymeric luminogens compared to monomers comprising primary or secondary amide functionality. [ 23 ]…”
Section: Terpolymer Ex Situ Monomers X1a) [Mol] X2b) [Mol] X3c) [Mmolmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 22 ] Indeed, a monomer bearing tertiary amide side chain should endow more rigidity and fluorescence of polymeric luminogens compared to monomers comprising primary or secondary amide functionality. [ 23 ]…”
Section: Terpolymer Ex Situ Monomers X1a) [Mol] X2b) [Mol] X3c) [Mmolmentioning
confidence: 99%
“…Notably, the surfactant‐free facile solution polymerization is better than that of surfactant‐assisted conventional emulsion polymerization for attaining the clusterization and AEE by the inter‐/intra‐molecular hydrogen bonding and hydrophobic interactions of polymers. [ 23 ] Here, N ‐(methylol)acrylamide (NMA) has been chosen as common comonomer for synthesizing P1 and P2 , as its side chain is expected to function as an in situ comonomer attachment site by the N–H activation. Moreover, NMA, a secondary amide with OH as hydrogen bonding site, can confer better rigidity in terpolymers.…”
Section: Terpolymer Ex Situ Monomers X1a) [Mol] X2b) [Mol] X3c) [Mmolmentioning
confidence: 99%
See 1 more Smart Citation
“…NTO Analysis. For determining individual electron property, 20 hole−electron wave function overlap (σ he ) and separation (Δr) between hole and electron distribution in S 1 , S 2 , and S 3 are envisaged in Table S14, wherein the results revealed local emissions (LEs)/CT transitions of 1, 2, and 3. The NTO results identified the exact locations of holes and electrons in terpolymers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Moreover, the larger wavelengths of emission maxima in DMSO compared to that in more polar CH 3 OH confirmed that hydrogen bonding interactions in polar protic solvents and polarity changed the peaks of ML1/ML2, and presented important roles in nonconventional intrinsic fluorescence of ML1/ML2. [54] The emissions (excitation-dependent) of ML1 and ML2 were confirmed by the shifting of spectra to higher λ em at larger wavelength of excitations (λ ex ) (Figure S6, Supporting Information). [55] In this regard, shifting toward higher λ em confirmed the presence of blue-emissive aggregates and emissive traps in each aggregate of ML1/ML2.…”
Section: Photophysical Studiesmentioning
confidence: 86%